Agricultural sustainability through Smart Farming Systems: A comparative Analysis Between the Republic of Korea and Republic of Uganda. - Happy, Kenneth; Gang, Roggers; Ban, Yeongjun; Yang, Sungyu; Rahmat, Endang; Okello, Denis; Komakech, Richard; Cyrus, Okello; Okello, Kalule David; Kang, Youngmin (Kabale University, 2024)
Smart farming involves the integration of information and communication technologies into machinery and sensors for use in agricultural systems. It is expected to potentially enhance the sustainability of agriculture and global food security. The need for smart farming arises from the increasing adverse environmental, ecological, social, and economic impacts on food systems. The potential impact of smart farming solutions on different countries is less known. Therefore, we comprehensively analyzed the role of smart farming solutions in sustaining agricultural production in the context of comparing a developed (Republic of Korea), and an emergent (Republic of Uganda) country. We scrutinized the agricultural assets, natural resources, approaches, technologies, policy interventions, achievements, challenges encountered, and reasons of smart farm pursuit for each country. Information presented in the paper indicated that both countries have similar objectives in the pursuit for smart farming: response to climate change and sustaining food security. However, the Republic of Korea employs a holistic approach of revolutionizing agriculture via smart farms. In contrast, distinct smart farming interventions implemented by government institutions, competing private sector, and non-governmental organizations are shaping the development of a smart farm concept in the Republic of Uganda. In conclusion, the application of smart farming solutions appears to be promising in enhancing the stability of the whole food system in both countries.